2014
DOI: 10.1519/jpt.0b013e318295daba
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Factors Affecting Gait Properties in Healthy Older Adults

Abstract: A decrease of knee extension strength and visual acuity and knee joint pain are factors affecting gait in the female older adults. Decreased knee extension strength and knee joint pain mainly affect respective distance and time parameters of the gait.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
1
12
0
1
Order By: Relevance
“…Pain has been linked to mobility deficits (Karttunen et al, 2012 ; Demura et al, 2014 ), and may disrupt the automaticity of walking through a number of mechanisms. One is intentional avoidance of pain (de Gier et al, 2003 ) in which an individual may consciously adjust his movements in order to minimize the occurrence of pain.…”
Section: Mechanistic Factors That Influence Automaticitymentioning
confidence: 99%
“…Pain has been linked to mobility deficits (Karttunen et al, 2012 ; Demura et al, 2014 ), and may disrupt the automaticity of walking through a number of mechanisms. One is intentional avoidance of pain (de Gier et al, 2003 ) in which an individual may consciously adjust his movements in order to minimize the occurrence of pain.…”
Section: Mechanistic Factors That Influence Automaticitymentioning
confidence: 99%
“…A recent survey in India reported that the prevalence of OA in the elderly over 65 years of age was 60.3% in urban populations and 32.6% in rural populations 3 ) , and knee OA affects approximately 9.3 million Americans 4 ) . Knee OA is accompanied by pain and weakening of the quadriceps in general 5 ) , and it affects a person’s walking ability 6 ) . The weakening of the quadriceps in particular makes the knee joint unstable, thereby resulting in less frequent use of the knee joint, and as a result, weakening of the muscle worsens 7 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Knee pain may cause fear of falls, and that has been found to cause gait changes in a knee OA population26,27,28 ) . The lack of any significant change in 6MWDs despite the improvements in aggravating pain score is probably due to the limited strengthening and cardiopulmonary-training components of Ai Chi.…”
Section: Discussionmentioning
confidence: 99%